(untitled) (Journal Of Educational and Psychological Researches, 2012)
The current study aimed to reveal the role of the high school (boys) in the Governorate of Qurayyat (KSA) in promoting intellectual security of students, and whether there were differences in the estimates of the study sample due to the variables; the current position, academic qualification, teaching specialization and years of experience. This study was conducted by applying the analytical descriptive method, and used questionnaire as a tool for data collection. The survey consisted of (44) items distributed on the four main axes: Principal, teacher, curriculum and extracurricular activities. The study sample consisted of (152) teachers, principals and supervisors. The results showed that the school plays a highly-positive role in promoting intellectual security in the axes of the principal, curriculum, teacher and a moderate role in the axis of the extracurricular activities. The study also showed that there were no statistically significant differences attributable to any of the variables of the study. In light of the results, the study provided a number of recommendations that aim to further activate the role of the school in promoting intellectual security.